APLIKASI SOFTWARE PENINGKATAN KUALITAS CITRA TERMOGRAM UNTUK EKSTRAKSI CIRI MENGGUNAKAN PARAMETER MSE DAN PSNR - Kusumadewi, Afriliana; Santoso, Sugeng (MAGISTRA, 2014)
Image enhancement is a fundamental part of image analysis. This research has a purpose to increase an image qualification for image extraction by image enhancement. Image enhancement which used in this research is filter Wiener and equalization histogram. This reaserch use data 10 normal breast thermogram image, 10 earlier breast cancer thermogram image, and 10 breast cancer stage of disease thermogram image. Pre processing of image done by altering thermogram colour image become thermogram grayscale image, determination of ROI and cropping method and then continued with image enhancement using filter Wiener and equalization histogram. The image result of image enhancement extracted using 6 level wavelet decomposition using daubechies2 wavelet. From extracted process is known the effect image enhancemet by using MSE and PSNR parameters. Keywords : Image Enhancement, Filter Wiener, Equalization Histogram, MSE, PSNR